2023
DOI: 10.1029/2022sw003308
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Strong Neutral Vertical Winds and Ionospheric Responses to the 2015 St. Patrick's Day Storm Using TIEGCM Driven by Data‐Assimilated Aurora and Electric Fields

Abstract: Joule heating and particle heating induced by particle precipitation are the two most important thermospheric heating sources in the auroral zones and compete with the solar irradiance during geomagnetic storm times (D. J. Knipp et al., 2004). Most of the energy deposited in the magnetosphere by the solar wind is ultimately dissipated in the ionosphere-thermosphere (I-T) system as a result of the convergence of Poynting flux and auroral particle precipitation that heats the atmosphere directly through collisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…X. Lu et al. (2021) assimilate ground‐based and space‐borne data to provide multi‐scale two‐dimensional electric field and particle precipitation patterns for the TIEGCM simulation of an intense geomagnetic storm. They discover strong vertical neutral winds when both the electric field and the particle precipitation are enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…X. Lu et al. (2021) assimilate ground‐based and space‐borne data to provide multi‐scale two‐dimensional electric field and particle precipitation patterns for the TIEGCM simulation of an intense geomagnetic storm. They discover strong vertical neutral winds when both the electric field and the particle precipitation are enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…found that the Global Ionosphere Thermosphere Model (GITM) driven by the THEMIS/ASI auroral observations better resolves the magnitude of TIDs (doubled) than that by empirical auroral inputs. Figure2shows a recent effort of comparing the TIEGCM runs with and without assimilated magnetospheric drivers (aurora and electric fields) during the 2015 St Patrick's Day storm(Lu et al, 2022). Data assimilation uses SuperDARN and PFISR ion drifts for electric fields, and SSUSI and THEMIS/ASIs data for aurora.…”
mentioning
confidence: 99%